2020
DOI: 10.1186/s40900-020-00201-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in doctoral research: reflections and experiences of the PPI contributors and researcher

Abstract: There is evidence in the literature showing that involving patients and the public in health research can have a positive influence on quality, relevance and impact of research. However, patients and the public are not always involved in all stages of the research. There is often no explanation as to why they were only involved in some stages of the research and not others. Additionally, there is often no description of researchers' or PPI contributor's experiences of involvement. This also raises another issu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 32 publications
6
69
0
Order By: Relevance
“…Investment in the PPIE partnership with patient and carer contributors is key, from the pre-funding stage of research through to the dissemination, and beyond the study (5, 6, 22, 61, 62). Our ndings show the need to tailor PPIE to preferences and values of research partners, and consideration has to be given to how variation in individual needs affects ongoing participation (11,12,14,63). Recent co-produced research recommends implementing costed external training, especially with regard to establish a relationship from the start (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investment in the PPIE partnership with patient and carer contributors is key, from the pre-funding stage of research through to the dissemination, and beyond the study (5, 6, 22, 61, 62). Our ndings show the need to tailor PPIE to preferences and values of research partners, and consideration has to be given to how variation in individual needs affects ongoing participation (11,12,14,63). Recent co-produced research recommends implementing costed external training, especially with regard to establish a relationship from the start (64).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have assessed how patients and carers can be meaningfully involved as contributors to research from prefunding, through to the end of the study and beyond (11)(12)(13), demonstrating the value of PPI and engagement (PPIE) input for shaping research and delivering impactful outcomes (13,14). The number of PPIE Journals are increasing (15), and the inclusion of the GRIPP2 reporting checklist and other tools have improved reporting, yet more needs to be done regarding impact assessment (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…However, while the importance of involving people is clear, 6 evidence-informed methods of doing so are lacking. 8,[11][12][13][14][15] A recent international consensus statement has defined a role for the public in 'data intensive' health research. 16 While in the health research discipline there are over 60 different reporting tools for this kind of data, most published tools are not used beyond the groups that developed them, and none work across multiple disciplines.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Working with the PPI panel provides the PhD scholars with opportunities for ongoing experiential learning in PPI, building on the formal PPI training provided in the CDA-MM. Incorporating PPI into doctoral research has been reported by PhD scholars as valuable 15 , with the potential to positively contribute to the development of both the doctoral research projects and the PhD scholars, while also being a rewarding experience for PPI contributors. 7 However it is not without its challenges, and the importance of training PhD scholars so they are equipped to overcome these challenges has been highlighted.…”
Section: Introductionmentioning
confidence: 99%